If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6X + 8) = 0 Reorder the terms: 7(8 + 6X) = 0 (8 * 7 + 6X * 7) = 0 (56 + 42X) = 0 Solving 56 + 42X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + 42X = 0 + -56 Combine like terms: 56 + -56 = 0 0 + 42X = 0 + -56 42X = 0 + -56 Combine like terms: 0 + -56 = -56 42X = -56 Divide each side by '42'. X = -1.333333333 Simplifying X = -1.333333333
| -47-2x=99-9x | | -5-x=-2x-6 | | 9u+2-3(-3-2)=2(u-5) | | n+46=47 | | 195=80x-5x^2 | | 15+h=-9+5h | | 2y^2+y-10= | | 4+(-8)-16-(-2)= | | 7.5+0.5m=30m | | 1.5625=(9+k)/k | | s/4=15 | | 0.06x-0.01y=3.3 | | 38=13b-14 | | b/3=12 | | 6(2z+3)+3z=22 | | 2(b+4)-(9+b)=-34 | | 2(9s+3)-3s=3(5s+2)-10 | | 6x-4-5x=0 | | y=-x^2+4x+7 | | (x^2)+x+1=0 | | 6x(2x-5)(x+5)=0 | | p-34=-21 | | 0=x^3-11x^2+39x-47 | | -2(y+2)=5y-8+2(4y+5) | | y=x^3-11x^2+39x-47 | | 18*2+x=6 | | 3x-9x=48 | | 7=-3+13+d | | Y^5z^4/y^6z^3 | | 10x^2+10=50 | | 9/10+3/5 | | 4/9*n=80 |